Stress and Depression: Are they Really Related? - Keerat; Jigyasha Sharma (Medsci Publications, 2024)
the term depression is commonly used to justify the emotional isolation. Common people do not see it as any different from stress or anxiety. Even emotional ventilation, such as crying, is sometimes said to be depression. I often hear suggestions of ventilating one's feelings or performing leisure activities to get rid of depression. Although, the importance of emotional ventilation can never be understated in order to manage mental health, according to the WHO, depression is a mental disorder that is identified by a loss of pleasure or interest in daily activities for a long period of time, the causes of which may vary from physical or emotional abuse to severe losses in life. Depression needs to be diagnosed and treated, whereas the misuse of the term may lead to misidentification and the illusion that talking to loved ones and getting indulged in one's favourite activities can cure it.